2003
DOI: 10.1038/sj.npp.1300161
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Activation of Mesolimbic Dopaminergic Neurons by Morphine Withdrawal Following Clonidine: Participation of Imidazoline and Norepinephrine Receptors

Abstract: The a2 adrenoceptor (a2R) agonist clonidine is used as a treatment for heroin addiction. Substantial evidence indicates that dopaminergic and noradrenergic systems have key roles in opiate dependence and withdrawal but the possible interactions between these two pathways remain unclear. The objective of this study was to establish the effects of clonidine pretreatment on ventral tegmental area dopaminergic (VTA DA) neuronal activity during morphine withdrawal. Responses of VTA DA neurons to withdrawal precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 64 publications
3
33
0
Order By: Relevance
“…This reduction of activity was biphasic: (1) the first rapid inhibition was maximal 30 s after the injection and was followed by a return to baseline activity (Fig. 4 F, trace); and (2) a second inhibition started 3 min after the injection and persisted for several hours [as reported previously (Georges and Aston-Jones, 2003)] (Fig. 4 E).…”
Section: The Activity Of Vta Da Neurons Is Higher In Morphine-dependementioning
confidence: 61%
“…This reduction of activity was biphasic: (1) the first rapid inhibition was maximal 30 s after the injection and was followed by a return to baseline activity (Fig. 4 F, trace); and (2) a second inhibition started 3 min after the injection and persisted for several hours [as reported previously (Georges and Aston-Jones, 2003)] (Fig. 4 E).…”
Section: The Activity Of Vta Da Neurons Is Higher In Morphine-dependementioning
confidence: 61%
“…However, clonidine is a mixed α 2 -noradrenergic and imidazoline-1 receptor agonist, whereas UK14304 is a selective α 2 receptor agonist (Andorn et al, 1988;Ernsberger et al, 1997;Georges et al, 2005;Georges and Aston-Jones, 2003). Therefore, the action of clonidine may be mediated by imidazoline receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we observed that 1 mg/kg of UK14304 produced a loss of muscle tone and sedation, indicating that behaviorally active doses were tested. Moreover, UK14304 (0.1 mg/ kg) decreased firing rates of rat locus coeruleus neurons immediately after an intraperitoneal injection in in vivo cell recordings, suggesting that the drug easily crossed the blood-brain barrier (Georges and Aston-Jones, 2003). UK14304 pretreatment (0.05 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore it has been shown that the BNST sends monosynaptic projections to dopaminergic VTA neurons to modulate reward (Georges and Aston-Jones, 2002). During withdrawal from morphine there is an inhibition of the firing of these dopaminergic cells that can not only be reversed with the a 2 -AR agonist clonidine, but potentiated by its administration (Georges and Aston-Jones, 2003). It is an interesting notion that the NET KO animals lack a mechanism (a 1 -AR LTD) that may contribute to the inhibition of the dopaminergic cells in the withdrawal state while simultaneously demonstrating increased behavioral sensitization and reward mediated behaviors to drugs of abuse.…”
Section: Ne Induces Ltd In a Time-dependent Mannermentioning
confidence: 99%